Fisheries development aim to increase earnings and prosperity socialize fishermen with remain to take care of sustainable of fish resources. One of pre-eminent commodity in territorial water of Pamekasan is anchovy. Anchovy catching in this region is done to use payang. Information about certainty of expense of investment and sum up advantage obtained in exploiting of anchovy resources with do not disregard its sustainability not yet been made available, so that needed by study of bio-technique - Moch Prihatna Sobari; Karyadi .; Diniah . (Buletin Ekonomi Perikanan, 2006)
Fisheries development aim to increase earnings and prosperity socialize fishermen with remain to take care of sustainable of fish resources. One of pre-eminent commodity in territorial water of Pamekasan is anchovy. Anchovy catching in this region is done to use payang. Information about certainty of expense of investment and sum up advantage obtained in exploiting of anchovy resources with do not disregard its sustainability not yet been made available, so that needed by study of bio-technique and financial. Actual effort and catch in 2004 each equal to 199,410 trips and 3,603,000 kilograms. Effort and catch at MSY condition each equal to 239.003 trips per year and 3,787,384.94 kilograms per year. Exploiting level in 2004 pursuant to MSY condition has reached number 95.13%. Mean investment of payang fishing unit equal to Rp30,570,000.00. Mean total cost released by Rp43,700,691.67, mean total revenue equal to Rp65,120,000.00, so that the fisherman mean profit equal to Rp21 ,419,308.33. RIC value is 1.49, payback period 1.43 year. NPV of during age of business activity of equal to Rp83,281 ,066.94, net B/C is 3.72, and IRR is 81.75%. With increase of price of solar diesel fuel, hence result of analysis sensitivity obtained by NPV of equal to Rp60,584,350.07, B/C of equal to 2.48 and IRR of equal to 65.29%. Pursuant to conducted analysis, hence the effort of fishing unit payang can be continued, but need of existence control from Department of Fishery and Marine Affair in clear licensing and arrangement hit effort conducted by fishery perpetrator (fishermen).